Fatal Hypermagnesemia: an acute ingestion of Epsom Salt in a patient with normal renal function - Muhammad Shoaib Khan; Sohaib Zahid; Muhammad Ishaq (Babol University of Medical Sciences, 2018)
Background: Generally, it is very rare for clinically significant hypermagnesemia to develop in an individual with normal renal functions as the renal handling of serum magnesium is a very potent process and it has the capacity, under conditions of hypermagnesemia, to completely block Mg (magnesium) reabsorption from the thick ascending limb of Henle. Therefore, hypermagnesemia usually arises in the setting of renal failure. Case presentation: We present a very rare case of a 40-year-old African American obese female with prior normal renal functions, who presented post-cardiac arrest following accidental overdose of Epsom salt. The patient was initially given supportive therapy and was later considered for the dialysis despite normal renal functions, as serum Mg levels kept on creeping up and clinical status kept on deteriorating continuously. Conclusions: Seemingly harmless magnesium containing (over-the-counter) (OTC) can potentially be lethal, and such consequences must always be taken into account when using such medications for a prolonged period of time.